Trimethylamine N-oxide predicts cardiovascular events in coronary artery disease patients with diabetes mellitus: a prospective cohort study - Yu, Xue; Wang, Yijia; Yang, Ruiyue; Wang, Zhe; Wang, Xinyue; Wang, Siming; Zhang, Wenduo; Dong, Jun; Chen, Wenxiang; Ji, Fusui; Gao, Wei (Frontiers in Endocrinology, 2024)
Background Gut microbiota has significant impact on the cardio-metabolism and inflammation, and is implicated in the pathogenesis and progression of atherosclerosis. However, the long-term prospective association between trimethylamine N-oxide (TMAO) level and major adverse clinical events (MACEs) in patients with coronary artery disease (CAD) with or without diabetes mellitus (DM) habitus remains to be investigated.This prospective, single-center cohort study enrolled 2090 hospitalized CAD patients confirmed by angiography at Beijing Hospital from 2017-2020.TMAO levels were performed using liquid chromatography-tandem mass spectrometry. The composite outcome of MACEs was identified by clinic visits or interviews annually. Multivariate Cox regression analysis, Kaplan-Meier analysis, and restricted cubic splines were mainly used to explore the relationship between TMAO levels and MACEs based on diabetes mellitus (DM) habitus.During the median follow-up period of 54 (41, 68) months, 266 (12.7%) developed MACEs. Higher TMAO levels, using the tertile cut-off value of 318.28 ng/mL, were significantly found to be positive dose-independent for developing MACEs, especially in patients with DM (HR 1.744, 95%CI 1.084-2.808, p = 0.022).MACEs among CAD patients with DM. The combination of TMAO in patients with CAD and DM is beneficial for risk stratification and prognosis.